REACTIVITY STUDY OF ACRYLAMIDE, BENZO[a]PYRENE, DCP, AND 3-MCPD AGAINST ADENINE AND GUANINE USING COMPUTATIONAL METHOD - RAHMADANI (NIM 10702025), ANGGA
Molecular study of DNA-carcinogen interaction can be carried out using different methods. Computational method is an alternative method to experimental methods which can be carried out in silico by applying computer program. This paper describes the reactivity study of acrylamide, benzo[a]pyrene, DCP and 3-MCPD, as food contaminants having carcinogenic potency, against adenine and guanine applying computational method available in HyperChem version 7.03 program. The carcinogenic properties of these contaminants can be predicted from their physico-chemicals parameters which can be calculated by computational method. In this research, semi-empirical and molecular mechanic method were applied. The calculation results showed that acrylamide has the lowest log P, molecular weight, and ionization energy among other contaminants, while 3-MCPD has the lowest steric hindrance among other contaminants. Acrylamide was predicted to be able to form the most stable adduct structure with adenine and guanine. Based on these results, acrylamide was predicted to be a contaminant with the highest carcinogenic potency. The carcinogenic potencies of the three contaminants, in descending reactivity , are as follow: acrylamide, 3-MCPD, benzo[a]pyrene, and DCP.